The abandoned empress. 8 - 인아; Yuna; 인아 (Yen Press, 2024)
"The moment Aristia was dreading is finally here--Jieun has arrived! As politics pit the two against each other yet again, she soon realizes that this Jieun is very different from the one she remembers . In order to protect herself and those dear to her, Tia hardens her resolve to walk the path of heir to House Monique ...until long-kept secrets are brought to light , calling her legitimacy as crown princess candidate into question! While the noble faction plans their next move with an openly hostile Jieun as their new pawn, Tia is reminded that within the palace, there is no room for mercy."--Back cover.